(3EYdGe GdSGFdjf Yf cJH SjO GdeQSdjfs - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3hHYO agPG JYdjb ejI CYdGe GdSGFdjf ef cJH SjO GdeQSdjf s
(3BNQgG (B:s
(3hcGf bJjHI Hf PhjH cGJH YHO Gdedc Hf eQhGf hcGf bjS Hf YWGQO cGJH GdhdjO Hf YbHI s
(3hgh ef eLehYI QSGFd dGHf Whdhfs
(3UhQJ HGdbGgQI SfI (B1345 (3Yf fSNI HNW GdeDda GSJYjQJ ef OeTbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B494 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B22 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs